Neoliberal discourses and ethnonormative regime in post-recognition Peru: redefining hierarchies and identities. - Callirgos, Juan Carlos (Cultural Studies, 2018)
This article analyses the impact of ‘recognition’ of cultural and ethnic diversity in Peru. It proposes that the rise of a new global ‘ethnonormativity’ - a regime to define and administrate cultural and identity differences, to establish boundaries between those who ‘are’ ethnic and those who are not, and to set rights and duties derived from identities - has had meagre effects in Peru. While the past decades have witnessed the emergence of Latin American political actors who regard indigenousness as their basic political identity, there has been no ‘emergence of indigenous movements’ in Peru. The discourses that highlight the importance of diversity have gained terrain - unsettling, to a certain extent, the narratives of assimilation through ‘development’ and mestizaje - and the Peruvian state has officially embraced ‘recognition’, including it in its official rhetoric and creating institutions to design policies to guarantee the rights of the indigenous and Afroperuvian ‘peoples’ (itself a label part of the language of multiculturalism). The state has also crafted a definition of ‘indigenous peoples’ and introduced ethnic variables in censuses and official statistics, thus being active in the production and regulation of subjects. Some civil society actors have also incorporated ethnic labels into their rhetoric to adapt to the global turn to identity politics. Peru remains, however, a fertile terrain for neoliberal policies and discourses of a different kind. A discourse that exalts ‘emprendedurismo’ (entrepreneurship) and states that success depends entirely on personal effort has become a new common sense, obscuring the structural inequality that has historically affected indigenous and Afroperuvian people. Extractivism continues to damage the environment and the rights of indigenous people, while the expansion of agribusiness in the coastal valleys of Peru keeps people - regardless of their ‘ethnic’ self-identification - in poverty and without basic labour and social rights. The article suggests that the ambiguities of the ethnonormative regime in Peru may serve as a diversion from structural issues in a context of neoliberalism and may re-elaborate racial hierarchies, racism and the narratives of mestizaje it allegedly opposes.